Respuesta :

Solve this by method of elimination where you make one term equal and then cancel it out.

36=-4y-11x  (Equation 1)
20=-10x-10y (Equation 2)

Reorganize the terms.
36=-11x-4y 
(Equation 1)
20=-10x-10y
 (Equation 2)

Multiply Equation 1 by 5 and Equation 2 by 2 to make y equal.
180=-55x-20y
40=-20x-20y

Now subtract Equation 2 from Equation 1. It is a bit messy but it looks like:
180-40=-55x-(-20x)-20y-(-20y)
180-40=-55+20x-20y+20y
140=-35x

We have now removed y from the equation, so we can now solve for x. Divide each side by -35 to find x.

140=-35x
-4=x

We have the equation 20=-10x-10y. Substitute -4 for x to solve for y.

20=-10x-10y
20=-10(-4)-10y
20=40-10y
-20=-10y
2=y

x=-4
y=2